Pengembangan Aplikasi Sistem Pemantauan Praktik Industri Berbasis Sinkronisasi di Sekolah Menengah Kejuruan - Agus Widodo; Budi Santosa; Muhammad Sayuti; Fitri Nur Mahmudah (Indo-MathEdu Intellectuals Journal, 2023)
The research aims to: (1) analyze the application of synchronization-based industrial practice systems at SMK Muhammadiyah I Playen; (2) develop a synchronization-based industrial practice system application at SMK Muhammadiyah I Playen; and (3) test the feasibility of the developed school synchronization-based industrial practice system application. The research uses research and development (R&D) methods using the codeigniter framework application. The subjects of the study included students of class XI TKJ SMK Muhammadiyah I Playen, Gunungkidul, Special Region of Yogyakarta. Data analysis uses quantitative analysis. The expected result is the application of industry practices that will be used to monitor students during industry practices based on the Codeigniter framework system. The results of the study include: (1) the PI monitoring system still uses conventional methods, monitoring guidance teachers directly come to the students to carry out PI. Students during attendance still use the presisnsi sheet held by the IDUKA supervisor, students also make activity journals on paper that has been provided by the school to fill in every day; (2) development of a PI monitoring system using the codeigniter framework application that makes it easier for guidance teachers, IDUKA supervisors and students to carry out PI implementation; and (3) a pilot of the PI monitoring system involving 56 students, five teachers, three IDUKA places is very easy to use and more effective